A Four-Level T-Type Neutral Point Piloted Inverter for Solar Energy Applications - Alnamer, Saddam Shueai; Mekhilef, Saad; Mokhlis, Hazlie (MDPI, 2018)
Multilevel inverters provide an output signal with low harmonic distortion and superior output voltages. This work proposes a new four-level T-type neutral point piloted (T-NPP) topology with higher efficiency and low total harmonic distortion (THD) and with the ability to withstand high voltage stresses, especially for high-power applications. The proposed topology is designed in such manner that the direct current (DC)-voltage stresses split over the components with strong possibilities to increase the load current and switching frequency. However, the operation of the proposed topology is based on two essential principles. The first principle is that each upper and lower switch of each leg consists of two insulated gate bipolar transistors (IGBTs) connected in series in order to withstand high voltage stresses and make it split over the two IGBTs in each switch. The second principle is using the DC-link circuit (T1 & T2) to generate 2Vdc and 1Vdc by connecting the bidirectional switches of each leg to the DC-link's mid-point. Furthermore, the proposed four-level T-NPP inverter outperforms other converters by the high number of output voltage level, low number of components, simple structure and higher efficiency. Finally, the proposed T-NPP topology concept was validated via simulation, experiments and theoretical analysis.